How uniformly the indian codes predict the shear strength of reinforced concrete beams? - Sundaresan, R.; Rao, G. Appa (Journal of Structural Engineering, 2025)
The current design expressions for shear recommended by majority of the codes of practice are based on the strength based approaches, in which the size dependence in evaluating the shear strength is not accounted for. Decrease in the nominal shear strength of Reinforced Concrete (RC) beams with the increase in depth of beams is a well known phenomenon. Despite several research efforts in this area, there doesn’t seem to be available a simple predictive expression applicable for all types of beams viz., deep, short and slender RC beams. The strut-and-tie model (STM) can be efficiently adopted to predict the shear strength of all types of beams. This paper reports on the use of the strut-and-tie model for predicting the shear strength of RC beams duly incorporating the size effect coefficient. The proposed predictive expression based on the refined strut-and-tie approach incorporating the size effect appears to estimate reasonably the ultimate strength of RC beams without shear reinforcements after cracking. The uniformity in margin of safety on the shear strength using the design expressions recommended by the Indian codes and the proposed equation in the present study has been ascertained from the huge experimental data base.